Does Employee Turnover Intervene Team Performance ? - Renwarin, Joseph M J; Putri, Alin Rizkiani; Astono, Anjar Dwi; Iskandar, Donant Alananto (BIMA Journal (Business, Management, & Accounting Journal), 2021)
This study describes the effect of leadership and teamwork on employee turnover and impact in team performance. The object of this research is PT Dreamaxtion Teknologi Internasional. This study uses a quantitative method through a questionnaire survey which was distributed directly to 60 respondents which was then processed using SPSS version 20.0 and the sampling method was non-probability sampling. The results of hypothesis testing (t test) that leadership has a significant effect on Team Performance with t count of 4.222 T table 2.002. Teamwork has a significant effect on Team Performance with t = 3.121 â‰¥ T table 2.002. And Turnover has no significant effect on Team Performance with t = 1.152 â‰¤ T table 2.002. Leadership and Teamwork have a significant effect on Team Performance while Employee Turnover has no significant effect on Team Performance. The implications of this research can provide an understanding for the management that although Turnover does not affect in Team Performance, it must still be considered, especially at PT Dreamaxtion Teknologi Internasional.